Seafood and Omega-3 Supplementation During Pregnancy and Lactation can be Considered Still Safe after Fukushima Nuclear Accident. - Gianluca, Di Luigi; Angela, D’Alfonso; Gaspare, Carta (Journal of Breastfeeding Biology, 2015)
Background: Scientific research is constantly expanding our knowledge of nutritional needs in pregnancy and lactation. In June 2014 the Food and Drug Administration (FDA) and the Environmental Protection Agency (EPA) issued draft-revised advice encouraging pregnant women, those who might become pregnant, breastfeeding mothers and young children to eat more fish, a total of least 8 ounces per week and to eat a variety of fish lower in mercury in particular anchovies, butterfish, catfish, clam, haddock (Atlantic), herring, mullet, oyster, perch (ocean), sardine, shad, trout (freshwater). However, the presence of radionuclides released from the damaged Fukushima Daiichi nuclear power plant in Pacific biota has aroused worldwide attention and concern. Objective and Methods: Evaluating all the scientific literature available after the Fukushima nuclear disaster, the aim of this review is to demonstrate the safety of seafood products and the use of omega-3 supplements potentially derived from contaminated radioactive fish. Results and Conclusions: There are no reasons to fear the amount of radiation in Japanese fish. The dose received from seafood consumption can be estimated to result in two additional fatal cancer cases per 10,000,000 similarly exposed people. The safest way to get omega-3 fatty acids during pregnancy is by taking a high-quality fish oil supplement, approved by a governing body that provides proof of quality such as the Council for Responsible Nutrition, the European Pharmocopeia Standard or the Norwegian Medicinal Standard and by the Food and Drug Administration or the Environmental Protection Agency 12. Pregnant and breastfeeding women do not need to cut fish out of their diet completely, and it may be safely eaten up to three times per week safely 3.
Keywords: Fish; Seafood; Omega-3 supplementation; Pregnancy; Lactation; Breast Feeding; Fukushima; Nuclear Disaster; Food and Drug Administration; Environmental Protection Agency.